Investment climate indicators for waste reuse enterprises in developing countries: application of analytical hierarchy process and goal programming model - Gebrezgabher, Solomie A.; Taron, A.; Amewu, Sena (Elsevier, 2019)
This study applied a combined analytical hierarchy process (AHP) and goal programming (GP) model to assist decision makers in identifying and prioritizing key investment climate (IC) indicators for waste recycling and reuse enterprises in developing countries. Taking a sector based perspective, key IC criteria and indicators were identified and ranked through country stakeholder workshops in Ghana and Kenya. Three different key decision maker groups namely government agencies, private waste reuse enterprises and non-governmental organizations (NGOs) were involved in identifying and ranking of IC criteria and indicators. The IC criteria identified were policy and infrastructure, finance, business support and markets. A number of indicators across each of the criteria were also identified. By incorporating qualitative and quantitative assessments, criteria and indicator rankings are determined using the AHP and GP model. Model results for Ghana revealed that both the private sector and NGO group ranked finance as the most important criterion while markets was the most important criterion for the government organization group. In contrast, none of the stakeholder groups in Kenya ranked finance as the most important criterion. This indicates that reform priorities of waste reuse sector vary across countries depending on the country’s current situation. The approach adopted in this study enables the criteria and indicators for assessing sector specific investment climate to be clearly identified and the decision making problem to be structured systematically. The exercise can be extended to other countries to elicit priority ranking of IC criteria and indicators for waste reuse enterprises.